Proteomic analysis of the plasmodium berghei gametocyte egressome and vesicular bioID of osmiophilic body proteins identifies merozoite TRAP-like protein (MTRAP) as an essential factor for parasite transmission - Kehrer, Jessica; Frischknecht, Friedrich; Mair, Gunnar R. (Molecular & cellular proteomics, 2016)
Malaria transmission from an infected host to the mosquito vector requires the uptake of intraerythrocytic sexual precursor cells into the mosquito midgut. For the release of mature extracellular gametes two membrane barriers—the parasite parasitophorous vacuole membrane and the host red blood cell membrane—need to be dissolved. Membrane lysis occurs after the release of proteins from specialized secretory vesicles including osmiophilic bodies. In this study we conducted proteomic analyses of the P. berghei gametocyte egressome and developed a vesicular bioID approach to identify hitherto unknown proteins with a potential function in gametocyte egress. This first Plasmodium gametocyte egressome includes the proteins released by the parasite during the lysis of the parasitophorous vacuole membrane and red blood cell membrane. BioID of the osmiophilic body protein MDV1/PEG3 revealed a vesicular proteome of these gametocyte-specific secretory vesicles. Fluorescent protein tagging and gene deletion approaches were employed to validate and identify a set of novel factors essential for this lysis and egress process. Our study provides the first in vivo bioID for a rodent malaria parasite and together with the first Plasmodium gametocyte egressome identifies MTRAP as a novel factor essential for mosquito transmission. Our data provide an important resource for proteins potentially involved in a key step of gametogenesis.
Gesehen am 07.05.2020